Software Architecture 7th European Conference, ECSA 2013, Montpellier, France, July 1-5, 2013, Proceedings - Drira, Khalil (Programming and Software Engineering, 2013)
This book constitutes the proceedings of the 7th European Conference on Software Architecture, ECSA 2013, held in Montpellier, France, in July 2013. The 25 full papers and 11 poster papers presented in this volume were carefully reviewed and selected from a total of 82 submissions. The contributions are organized in topical sections named: architectural and design patterns and models; ADLs and architectural MetaModels; architectural design decision-making; software architecture conformance and quality; and architectural repair and adaptation.